What can seismic noise tell us about the Alpine reactivation of the Iberian Massif? An example in the Iberian Central System - J. Andrés; J. Andrés; P. Ayarza; M. Schimmel; I. Palomeras; M. Ruiz; R. Carbonell (Solid Earth, 2020)
The Iberian Central System, formed after the Alpine reactivation of the Variscan Iberian Massif, features maximum altitudes of 2500 m. It is surrounded by two foreland basins with contrasting elevation: the Duero Basin to the north, located at 750–800 m, and the Tajo Basin to the south, lying at 450–500 m. The deep crustal structure of this mountain range seems to be characterized by the existence of a moderate crustal root that provides isostatic support for its topography. New seismic data are able to constrain the geometry of this crustal root, which appears to be defined by a northward lower-crustal imbrication of the southern Central Iberian crust underneath this range. Contrarily to what was expected, this imbrication also affects the upper crust, as the existing orogen-scale mid-crustal Variscan detachment was probably assimilated during the Carboniferous crustal melting that gave rise to the Central System batholith. In addition, the lower crust might have thinned, allowing coupled deformation at both crustal levels. This implies that the reactivated upper-crustal fractures can reach lower-crustal depths, thus allowing the entire crust to sink. This new model can explain the differences in topography between the Central System foreland basins. Also, it provides further constraints on the crustal geometry of this mountain range, as it seems to be that of an asymmetric Alpine-type orogen, thus hindering the existence of buckling processes as the sole origin of the deformation. The results presented here have been achieved after autocorrelation of seismic noise along the CIMDEF (Central Iberian Massif DEFormation Mechanisms) profile. Although the resolution of the dataset features limited resolution (0.5–4 Hz, stations placed at ∼ 5 km), this methodology has allowed us to pinpoint some key structures that helped to constraint the deformation mechanisms that affected Central Iberia during the Alpine orogeny.